1986
DOI: 10.2307/1960858
|View full text |Cite
|
Sign up to set email alerts
|

An Evolutionary Approach to Norms

Abstract: Norms provide a powerful mechanism for regulating conflict in groups, even when there are more than two people and no central authority. This paper investigates the emergence and stability of behavioral norms in the context of a game played by people of limited rationality. The dynamics of this new norms game are analyzed with a computer simulation based upon the evolutionary principle that strategies shown to be relatively effective will be used more in the future than less effective strategies. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
665
1
12

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,342 publications
(689 citation statements)
references
References 15 publications
11
665
1
12
Order By: Relevance
“…6. The process outlined here parallels results obtained by Axelrod (1986) in a simulation of the evolution of group norms. Although Axelrod did not assign special weight to the initial defections from norms, his model assumes that successful disobedience will lead to a proliferation of violations.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…6. The process outlined here parallels results obtained by Axelrod (1986) in a simulation of the evolution of group norms. Although Axelrod did not assign special weight to the initial defections from norms, his model assumes that successful disobedience will lead to a proliferation of violations.…”
Section: Resultssupporting
confidence: 55%
“…Once group members begin to expect cooperation from one another, norms of cooperation and fairness are likely to develop. Axelrod (1986) has suggested that modes of conduct which have favorable outcomes for the people who pursue them tend to evolve into group norms. Public-spirited action that serves self-interest could therefore engender a principled attachment to the common good, undermining the assumption of self-interestedness that gives the logic of collective action its bite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That interation should facilitate cooperation (vis-~t-vis a one shot setting) is the standard theoretical conjecture (cf., Axelrod, 1984Axelrod, , 1986. One of Olson's points in the Rise andDecline of Nations is that, over time, ingroups can mobilize rewards, punishments, and selective incentives which induce greater amounts of cooperative behavior.…”
Section: Notesmentioning
confidence: 99%
“…A classic example is Axelrod's 1986 paper [60] where he investigated norms emerging as successful strategies in situations described by game theory. Axelrod let the norms evolve by genetic algorithms (an algorithmic framework for optimization inspired by genetics).…”
Section: Political Sciencementioning
confidence: 99%